The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12983/ijsrk-2014-p0265-0276
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Sulphur Dioxide Emissions and Local Environment Pollution

Abstract: Abstract. During the last 30 years Chinese economy has increased rapidly. The pollution of air in many Chinese cities exceeds both national and international standards due to rapid urbanization, industrialization and increased energy consumption. At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Regarding the physicochemical conditions of the water resources present in the proposed corridor, it was observed that the margin of the water course has an anthropized riparian forest, which causes modi cation of the characteristics and the quality of the resource. In addition to causing siltation in the stretch with access to the river, temperature is a factor with the potential to control the concentration of dissolved oxygen and prevent bacteria from consuming the existing oxygen; and stretches with inadequate values should be monitored frequently ( Due to the pH presenting alterations in the analyzed sections, acidi ed freshwater environments may be related to natural characteristics of the environment or may be suffering the in uence of acid rain (Beaune et al 2018;Mohajan 2018). These occur in spaces with a predominance of urbanized areas and rural properties, which may reveal an effect of their activities and may be related to the increase in heavy metals affecting aquatic organisms (Bobkova et al 2015;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the physicochemical conditions of the water resources present in the proposed corridor, it was observed that the margin of the water course has an anthropized riparian forest, which causes modi cation of the characteristics and the quality of the resource. In addition to causing siltation in the stretch with access to the river, temperature is a factor with the potential to control the concentration of dissolved oxygen and prevent bacteria from consuming the existing oxygen; and stretches with inadequate values should be monitored frequently ( Due to the pH presenting alterations in the analyzed sections, acidi ed freshwater environments may be related to natural characteristics of the environment or may be suffering the in uence of acid rain (Beaune et al 2018;Mohajan 2018). These occur in spaces with a predominance of urbanized areas and rural properties, which may reveal an effect of their activities and may be related to the increase in heavy metals affecting aquatic organisms (Bobkova et al 2015;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These gasses have the ability to cause damage in the CCUS system especially to the production equipment and pipelines by either turning sour on its own or by reacting with water to produce corrosive sulphuric acid (H 2 SO 4 ) (De Visser et al 2008;Intergovernmental Panel on Climate Change 2015;Schwartz 1989;SNC-Lavalin Inc 2004). Usually, when fossil fuel or coal is combusted, it will produce a high concentration of these acidic gas which if it is release to the atmosphere, it can cause acid rain (Mohajan 2019). Thus, a strong and stable storage are needed to prevent leak, as it will release toxic gases to the atmosphere and endanger everything in the surrounding (Intergovernmental Panel on Climate Change 2015; SNC-Lavalin Inc 2004).…”
Section: Sulphur Oxides (So X ) and Hydrogen Sulphide (H 2 S)mentioning
confidence: 99%
“…The strategic shift from emission control to air quality management is evident in China's three decades of air pollution progress. The worsening acid rain problem in China was fixed in 2007 by regulating sulfur dioxide (SO2) emissions [11]. Since 2013, control activities on numerous precursors and sectors have aimed to lower PM2.5 concentrations, signalling a shift in focus from emissions to air quality.…”
Section: Progress Of Air Pollution In Chinamentioning
confidence: 99%